Ethnozoological knowledge of diversity, folk taxonomy, and animal hunting among the Baduy in Banten, Indonesia - BUDIAWATI SUPANGKAT ISKANDAR; JOHAN ISKANDAR; DEDE MULYANTO; JATNA SUPRIATNA (Society for Indonesian Biodiversity, 2024)
Abstract. Iskandar BS, Iskandar J, Mulyanto D, Supriatna J. 2024. Ethnozoological knowledge of diversity, folk taxonomy, and animal hunting among the Baduy in Banten, Indonesia. Biodiversitas 25: 5031-5045. Presently, biocultural systems, an emergent ecosystem, are experiencing significant growth in traditional villages due to the presence of natural resources. Baduy, a sacred community rich in natural and environmental resources, has a high diversity of animals, which needs to be managed based on their unique Traditional Ecological Knowledge (TEK) and beliefs. Therefore, this research focused on the TEK of the community on animal diversity, folk taxonomy, and wildlife hunting. The qualitative with an ethnozoological method was used with data collected from field observation, semi-structured interviews with informants, and participant observation. We found 90 species of birds, 16 mammals, 14 fishes, 10 insects, and 9 reptiles known by the Baduy in Banten, Indonesia and at least 3 taxa levels of Baduy zoological classification. The primary, secondary, and third taxa represented life forms, species, and races or sub-species. Animals can be classified based on their distinctive morphological characteristics, specific behavior, time activity, special habitat, and functions. The hunting of animals carried out by the Inner Baduy community was in accordance with customary rules supervised by informal Baduy leaders. However, unlike the Inner Baduy, Outer Baduy has hunted wild animals for semi-commercial purposes instead of subsistence purposes. In conclusion, safeguarding the Baduy people's land, language, and culture plays an important role in conserving animals in the rural ecosystem of the traditional communities.